Analisa Penggunaan Kriteria Integral Galat Minimum ITSE Untuk Menemukan Parameter Kontrol PID Pada AVR Menggunakan Algoritma PSO - Ari Asriyanto; Nurhalim Nurhalim (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
The automatic voltage regulator (AVR) is a major component in generating electrical energy. To improve the performance of the AVR system, controlling the proportional integral derivative (PID)is needed because it has a simple structure, is very strong in system variations, and easy to understand. The main problem for the PID controller is determining the appropriate parametervalues for the values of the proportional constant (Kp), the integral constant (Ki), and the differential constant (Kd) to obtain the optimal transient response. In the conventional methodbased on trial and error, a more efficient method is needed, namely Particle Swarm Optimization (PSO), an optimization method based on a flock of bird population. The criteria the minimum errorintegral used as a fitness function in the PSO is the integral of time multiplied by squared error (ITSE). The parameter values used must meet the stability requirements, namely the stability characteristics of the Root Locus. PID control has a significant impact on the plant, this can be seen from the results that have a good level of stability. As for the criteria using the PSO-ITSEalgorithm has a better transient response. In finding these values and analysis using the Matlab software tools.Keywords:AVR, PSO, ITSE, Root Locus. transient response, Matlab